Comparative Analysis for the Maintenance Phase of Depth of Anesthesia: Decentralized or Decoupled? - Hegedus, Erwin T.; Mihai, Marcian D.; Othman, Ghada Ben; Copot, Dana; Birs, Isabela R.; Muresan, Cristina I. (2024 4th International Conference on Electrical, Computer, Communications and Mechatronics Engineering (ICECCME), 2024)
General anesthesia requires precise control of both anesthetic depth and hemodynamic stability to ensure patient safety. The interactions between anesthetic and hemodynamic drugs can complicate this process, making it crucial to optimize control strategies. This paper presents a comparative analysis between two control strategies-decentralized and decoupled approaches-for the maintenance phase of general anesthesia, focusing on reducing interactions between the subsystems controlling the depth of anesthesia and hemodynamic parameters. A fractional-order PID controller is employed to implement the decoupled strategy, aiming to minimize cross-effects between anesthetic and hemodynamic drugs. The performance of this approach is evaluated against the decentralized strategy using a benchmark model and patient data from 24 virtual subjects. Results indicate that the decoupled approach offers superior disturbance rejection and control stability. The findings suggest that this strategy can enhance patient safety and surgical outcomes by improving the precision of anesthetic administration.